Old and in pain: Enduring and situational effects of cultural aging stereotypes on older people's pain experiences. (28th November 2014) - Bernardes, S.F.; Marques, S.; Matos, M.
Abstract Background This study aimed to investigate the interplay between enduring and situational aging stereotype (AS) effects in older adults' self‐reports of clinical and experimentally induced pain. We expected that, as compared with the situational activation of positive AS or a neutral condition, the activation of negative AS would lead to more severe self‐reports of clinical pain (H1, hypothesis 1), higher cold pressor task (CPT) pain threshold (H2) and lower CPT pain tolerance (H3), especially among older adults who more strongly endorsed AS. Methods This was a prospective study across two moments in time. At time 1 (T1), 52 older adults (Mage = 74.7; 51.9% women) filled out measures of cultural AS endorsement, clinical pain severity and interference. Three months afterwards (T2), some of these participants collaborated in an experimental study on the effects of AS activation on reported clinical pain (n = 40) and experimentally induced (using CPT) pain threshold and tolerance (n = 35). Results Our results supported H2, i.e., as compared with the activation of positive AS or a neutral condition, when negative AS were activated older adults showed higher CPT pain thresholds, but this effect was more salient among those who more strongly endorsed AS at T1. Conclusions This study stresses the influence of cultural AS in older adults' pain experiences showing that the situational activation of negative AS greatly increases experimentally induced pain thresholds of elders who more strongly endorse those stereotypes. It also highlights the relevance of interventions at the level of the physical and/or social environments surrounding elders in pain.